Primary Bovine Extra-Embryonic Cultured Cells: A New Resource for the Study of In Vivo Peri-Implanting Phenotypes and Mesoderm Formation - Hue, Isabelle; Evain-Brion, Danièle; Fournier, Thierry; Degrelle, Séverine A. (PLOS ONE, 2015)
In addition to nourishing the embryo, extra-embryonic tissues (EETs) contribute to early embryonic patterning, primitive hematopoiesis, and fetal health. These tissues are of major importance for human medicine, as well as for efforts to improve livestock efficiency, but they remain incompletely understood. In bovines, EETs are accessible easily, in large amounts, and prior to implantation. We took advantage of this system to describe, in vitro and in vivo, the cell types present in bovine EETs at Day 18 of development. Specifically, we characterized the gene expression patterns and phenotypes of bovine extra-embryonic ectoderm (or trophoblast; bTC), endoderm (bXEC), and mesoderm (bXMC) cells in culture and compared them to their respective in vivo micro-dissected cells. After a week of culture, certain characteristics (e.g., gene expression) of the in vitro cells were altered with respect to the in vivo cells, but we were able to identify “cores” of cell-type-specific (and substrate-independent) genes that were shared between in vitro and in vivo samples. In addition, many cellular phenotypes were cell-type-specific with regard to extracellular adhesion. We evaluated the ability of individual bXMCs to migrate and spread on micro-patterns, and observed that they easily adapted to diverse environments, similar to in vivo EE mesoderm cells, which encounter different EE epithelia to form chorion, yolk sac, and allantois. With these tissue interactions, different functions arose that were detected in silico and corroborated in vivo at D21–D25. Moreover, analysis of bXMCs allowed us to identify the EE cell ring surrounding the embryonic disc (ED) at D14-15 as mesoderm cells, which had been hypothesized but not shown prior to this study. We envision these data will serve as a major resource for the future in the analysis of peri-implanting phenotypes in response to the maternal metabolism and contribute to subsequent studies of placental/fetal development in eutherians.